Functional mining of the crotalus Spp. Venom protease repertoire reveals potential for chronic wound therapeutics - Meléndez-Martínez, David; Plenge Tellechea, Luis Fernando; Gatica Colima, Ana Bertha; Cruz-Pérez, Martha Sandra; Aguilar-Yáñez, José Manuel; Licona-Cassani, Cuauhtémoc (2020)
Chronic wounds are a major health problem that cause millions of dollars in expenses every year. Among all the treatments used, active wound treatments such as enzymatic treatments represent a cheaper and specific option with a fast growth category in the market. In particular, bacterial and plant proteases have been employed due to their homology to human proteases, which drive the normal wound healing process. However, the use of these proteases has demonstrated results with low reproducibility. Therefore, alternative sources of proteases such as snake venom have been proposed. Here, we performed a functional mining of proteases from rattlesnakes (Crotalus ornatus, C. molossus nigrescens, C. scutulatus, and C. atrox) due to their high protease predominance and similarity to native proteases. To characterize Crotalus spp. Proteases, we performed di erent protease assays to measure and confirm the presence of metalloproteases and serine proteases, such as the universal protease assay and zymography, using several substrates such as gelatin, casein, hemoglobin, L-TAME, fibrinogen, and fibrin. We found that all our venom extracts degraded casein, gelatin, L-TAME, fibrinogen, and fibrin, but not hemoglobin. Crotalus ornatus and C. m. nigrescens extracts were the most proteolytic venoms among the samples. Particularly, C. ornatus predominantly possessed low molecular weight proteases (P-I metalloproteases). Our results demonstrated the presence of metalloproteases capable of degrading gelatin (a collagen derivative) and fibrin clots, whereas serine proteases were capable of degrading fibrinogen-generating fibrin clots, mimicking thrombin activity. Moreover, we demonstrated that Crotalus spp. are a valuable source of proteases that can aid chronic wound-healing treatments.